2015
DOI: 10.3390/sym7010241
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Obliqueness of Angles as a Cue to Planar Surface Slant Found in Extremely Simple Symmetrical Shapes

Abstract: Abstract:The Necker cube is a striking example for perceptual dominance of 3D over 2D. Object symmetry and obliqueness of angles are co-varying cues that may underlie the perceived slant of Necker cubes. To investigate the power of the oblique-angle cue, slants were judged of extremely simple symmetrical shapes. Slant computations based on an assumption of orthogonality were made for two abutting lines as a function of vertex angle and the slant of the screen. Computed slants were compared with slants judged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…between the sets of parallel edges becomes closer to perpendicular on the plane with the perceived orientation (see also Saunders & Knill, 2001Griffiths & Zaidi, 2000Erkelens, 2013 for similar observations). Erkelens (2015) also showed this bias on the perceived orientation of a plane in a 3D scene by using an isosceles triangle and a T-junction.…”
Section: Perception Of a Perpendicular Anglementioning
confidence: 77%
See 2 more Smart Citations
“…between the sets of parallel edges becomes closer to perpendicular on the plane with the perceived orientation (see also Saunders & Knill, 2001Griffiths & Zaidi, 2000Erkelens, 2013 for similar observations). Erkelens (2015) also showed this bias on the perceived orientation of a plane in a 3D scene by using an isosceles triangle and a T-junction.…”
Section: Perception Of a Perpendicular Anglementioning
confidence: 77%
“…A pair of parallel lines in a 3D scene are projected to a pair of converging lines B and C in the figure that forms a perpendicular angle. But, the angles of the converging lines is underestimated and the angle of B and C is not perceived as perpendicular (Erkelens, 2015;Osa et al, 2011). between the sets of parallel edges becomes closer to perpendicular on the plane with the perceived orientation (see also Saunders & Knill, 2001Griffiths & Zaidi, 2000Erkelens, 2013 for similar observations).…”
Section: Perception Of a Perpendicular Anglementioning
confidence: 95%
See 1 more Smart Citation
“…These feature points are inherent in the 3D objects present in the scene. Note that: (i) the shapes and positions of these objects often satisfy a number of a priori constraints, and (ii) the visual system can make use of these a priori constraints to recover a 3D scene from its 2D representation on the retina [ 4 , 5 , 6 , 7 ] (see Reference [ 50 ] for example). In light of these facts, it is questionable that many, if any, inferences about the visual system can be generalized to the veridical perception observed in our everyday life from the non-veridical perceptions that have been observed in many psychophysical studies that used very simple visual stimuli, such as triangles, ellipses, and planes that intersect the interocular axis perpendicularly, or are coplanar with the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…A perpendicular junction in a 3D scene can be projected to a junction with any angle in the 2D image, but this depends on the orientation of the junction in the scene. It has been shown that the perception of a 3D shape from a 2D contour drawing is biased to make the 3D shape have perpendicular junctions (Erkelens, 2015), and to make the faces of the 3D shape form perpendicular corners (Perkins, 1972;Perkins, 1976;Sugihara, 1997Sugihara, , 2005Sugihara, , 2014bGriffiths & Zaidi, 2000).…”
Section: Discussionmentioning
confidence: 99%